Effects of Monsoon Circulation on Bedload Transport in the Qiongzhou Strait and Adjacent Seas Based on SCHISM - Yuxin Huang; Xiangbai Wu; Huan Mei; Shouxian Zhu; Changliang Tong; Xinyi La (Journal of Marine Science and Engineering)
This study quantitatively investigates monsoon-driven bedload sediment transport mechanisms in the Qiongzhou Strait using the SCHISM model, revealing three key findings: (1) Monsoon seasonality governs net sediment flux through contrasting hydrodynamic regimes, with the winter monsoon establishing spatially coherent westward transport pathways, while the summer monsoon induces counteracting flow patterns that suppress net transport. (2) Winter conditions exhibit opposing transport vectors between tidal and monsoon forcing at both strait entrances, with monsoon dominance at the western entrance contrasting tidal predominance in the eastern sector. (3) Summer monsoon–tide hydrodynamic decoupling results in transport magnitudes ≤ 10% of tidal-driven quantities across critical cross-sections. The research elucidates sediment budget partitioning mechanisms in monsoon-dominated shelf seas, particularly revealing a spatial reversal of dominant transport drivers between eastern and western gateways that mechanistically explains observed sedimentary architecture asymmetries. By innovatively quantifying spatiotemporal coupling effects of meteorological and tidal forcing, this work advances theoretical understanding of sediment flux allocation under monsoonal systems and provides scientific support for seabed resource management and geomorphological evolution predictions.